1998
DOI: 10.1038/sj.cdd.4400437
|View full text |Cite
|
Sign up to set email alerts
|

Differential apoptotic response of human melanoma cells to 1α,25-dihydroxyvitamin D3 and its analogues

Abstract: Pleiotropic actions of the biologically active form of vitamin D 3 , 1a,25-dihydroxyvitamin D 3 (VD), include antiproliferative effects in both normal human melanocytes and malignant melanoma cell lines. In this study the actions of VD and its low calcemic analogues EB1089 and CB1093, have been examined in two human melanoma cell lines MeWo and WM1341. Both cell lines express similar amounts of vitamin D receptor mRNA and show functional gene regulatory effects in response to VD and its analogues. VD, EB1089 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
4
77
0
Order By: Relevance
“…Next we asked how the southern (46-50 N), middle (51)(52)(53)(54)(55) N), northern (56-60 N), and northernmost (>60 N) European countries' CMM incidences changed over time to learn if the increase is linear or exponential in every latitudinal region. We only included countries with more than 50% of the available data (Table 2) in Figure 2 so as not to skew the slopes of the trendlines by data that was only collected in the later years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next we asked how the southern (46-50 N), middle (51)(52)(53)(54)(55) N), northern (56-60 N), and northernmost (>60 N) European countries' CMM incidences changed over time to learn if the increase is linear or exponential in every latitudinal region. We only included countries with more than 50% of the available data (Table 2) in Figure 2 so as not to skew the slopes of the trendlines by data that was only collected in the later years.…”
Section: Resultsmentioning
confidence: 99%
“…To show a lack of bias, we also analyzed the data of all the countries listed inTable 1A and included Italy, Spain, and Portugal and found a similar exponential increase in the CMM incidences with a slightly reduced slope (results not shown). The temporal data in Figure 2 was plotted from the averaged data in Figure 3, we compare female and males in the northern (averaged [46][47][48][49][50][51][52][53][54][55] N for »50 N) and southern (averaged all countries above 55 N for »60 N) regions of Europe from the averaged data in Table 3. In some of our analyses ( Table 1A), western Europe <17 E (Table 1B), and eastern Europe >17 E ( Table 1C).…”
Section: Temporal Analysismentioning
confidence: 99%
“…Vitamin D has been shown to inhibit proliferation and induce differentiation in some melanoma cells, although melanoma cell lines have demonstrated resistance to vitamin D growth arrest (Danielsson et al, 1998(Danielsson et al, ,1999Reichrath et al, 2007). A population-based study of 528 melanoma cases found that the presence of solar elastosis (dermal sun damage) was associated with a better prognosis for melanoma patients (Berwick et al, 2005).…”
Section: Vitamin D and Potential Protective Effects Of Chronic Sun Exmentioning
confidence: 99%
“…[15] Furthermore, outdoor workers have twice the vitamin D 3 levels as indoor workers [16] and they have about half the risk for getting CMM. [17] And along with providing another apoptotic pathway for melanoma cells through the vitamin D 3 receptor, [13] vitamin D 3 boosts the immune system by enabling T cells to become activated so they can kill virally infected and malignant cells. [18] Paradoxically, in Europe, we found significantly higher CMM incidences occur with lower UVB doses [8] and besides suggesting lower levels of vitamin D may be involved, the findings could also implicate higher levels of UVA exposure in the etiology, as we and others have previously hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…[10] HPV expedients transformation by inactivating p53, pRB, and vitamin D 3 receptor initiated apoptotic pathways so that the cell survives even with DNA damage. [11][12][13] The importance of vitamin D is reflected by the fact that CMM patients had deficient and insufficient prediagnostic vitamin D 3 levels [14] and survived longer if they got regular sun exposures. [15] Furthermore, outdoor workers have twice the vitamin D 3 levels as indoor workers [16] and they have about half the risk for getting CMM.…”
Section: Introductionmentioning
confidence: 99%